Political Corruption, Democratic Theory, and Democracy - Navot, Doron (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2014)
According to recent conceptual proposals, institutional corruption should be understood within the boundaries of the institution and its purpose. Political corruption in democracies, prominent scholars suggest, is characterized by the violation of institutional ideals or behaviors that tend to harm democratic processes and institutions. This paper rejects the idea that compromises, preferences, political agreements, or consent can be the baseline of conceptualization of political corruption. In order to improve the identification of abuse of power, the concept of political corruption should not be related directly to democratic institutions and processes; rather, it should be related to ideals whose content is independent of citizens’ preferences, institutions and processes. More specifically, I articulate the relations between political corruption and the notion of subjection, and include powerful citizens in the category of political corruption. Yet, I also suggest redefining under what conditions agents are culpable for their motivations in promoting private gain. By doing this, we better realize how democratic institutions can be the source of corruption and not just its victims. Such a redefinition, I propose finally, is the basis for the distinction between individual and institutional corruption.